New forms of migration into the European south: challenges for citizenship and governance: the Portuguese case - Fonseca, Maria Lucinda (2002)
Since the mid‐1980s, Portugal has altered its position in the international migration context. It is no longer exclusively an emigration country but has also become a receiving nation, hosting people from its former African colonies, and more recently from Brazil and Eastern Europe. This has caused significant changes in Portuguese society, which is nowadays socially more diverse and ethnically richer. This paper identifies the most important challenges to citizenship and governance in Portugal, focusing on: (a) the changes in the national laws regulating immigration; (b) the measures adopted by central government to fight discrimination; and (c) the growing social exclusion faced by many immigrants. Among the adopted measures, the new law regulating the entry and permanence of foreigners in Portugal, the establishment of a High Commissioner for Immigration and Ethnic Minorities (ACIME), the growing role of immigrants' associations, and the responsibilities transferred to local authorities are closely analysed. Drawing on analysis of interviews and questionnaires addressed to civil servants working in departments related to immigration as well as on reports published by municipalities in the Lisbon Metropolitan Area (LMA), the article also investigates the strategies adopted by local authorities to promote the successful integration of immigrants. The evidence indicates that there is a growing feeling among local authorities that their resources should be oriented to work with the citizens and not just for the citizens. To guarantee future sustainable development, citizens, regardless of their geographical origin, should have a say in the decision‐making processes at a local level.